(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Background: In type 2 diabetes mellitus (DM2), hyperglycemia activates the polyol pathway of glucose metabolism, resulting in accumulation of sorbitol and fructose. Polymorphism of aldose reductase (a key enzyme of the poliol pathway) gene (AKR1B1) influences the activity of the polyol pathway and might be associated with the development of diabetic retinopathy (DR). Purpose: To identify any association of the polymorphisms influencing the activity of aldose reductase gene (rs759853 and rs9640883 of AKR1B1) with DR in the Ukrainian population. Materials and Methods: In total, 311 individuals were involved in the study. Group 1 (control group) was composed of 107 ophthalmologically normal subjects. Group 2 contained 76 patients with stage 1 DR (i.e., showing no fundus changes). Group 3 consisted of 64 patients diagnosed with non-proliferative DR (NPDR), and Group 4 was composed of 64 patients diagnosed with proliferative DR (PDR). The TaqMan Mutation Detection Assays were used to analyze polymorphic DNA loci in a Real-Time PCR System 7500. Results and Discussion: In Ukrainian population, rs759853 and rs9640883 of AKR1B1 were associated with the development of DR. The mutant A allele and AA genotype at the rs759853 increased the odds (OR=2.8 and OR=5.2, respectively; р<0.001) of developing DR. In addition, the ancestral G allele and the homozygous G/G status at the rs9640883 increased the odds (OR=2.6 and OR=3.0, respectively; р<0.001) of developing DR. The presence of risk alleles had a negative effect on the development of DR in DM2. The AKR1B1 rs759853 and rs9640883 had no effect on the development of PDR. Importance of the polymorphisms for the development of DR was demonstrated by dispersion analysis (rs759853: F = 18.9, p < 0.001; rs9640883: F = 6.9, p = 0.001). Conclusion: The frequency of the ancestral G allele of the AKR1B1 rs759853 significantly decreased, whereas that of the mutant A allele increased with increased severity of pathological process in DR. The frequency of the ancestral GG genotype of the AKR1B1 rs9640883 was significantly elevated, whereas that of the heterozygous GA genotype was decreased, and minor homozygous AA genotype was absent in diabetes patients with DR.